Isokinetic assessment of lower extremities in Chinese elite male figure skaters - Wang, Y.; Liu, D. (Exercise Biochemistry Review, 2018)
Objective Figure skating is a kind of sport that is a unique combination of art and athleticism. In recent years, the increased emphasis on jumping skills has become apparent, the number of quadruple jump in 2018 winter olympic game was 2.2 times in short program and 2.5 times in long program in the top six male figure skating athletes`s program choreography compared with the 2014.The demand for more jumping skills has resulted in an increased demand for lower extremity strength, power, and "power endurance" to achieve high-difficulty skills while fatigued.But there are few researches about the strength characteristics of figure skaters.. Present research project aimed to analyse the characteristic of lower extremities strength of chinese elite male figure skaters.